اثر التراث العربي و الغربي في الادب الملايوي = The influence of Arabic and Western tradition in the Malay literature - Yaacob, Adli (IIUM Press, 2019)
هتم هذه المقالة بالأثر الذي تركته اللغة العربية واللغة الإنجليزية في اللغة الملايوية؛ إذ فتأثرت اللغة الملايوية منذ البداية باللغة العربية، واقترضت منها كلمات كثيرة، واستعملت في كتابتها الحروف الهجائية العربية "الجاوية"، وذلك يرجع إلى العلماء الملايويين الأوائل الذين تلقوا تعليم اللغة العربية والدراسات الإسلامية في البلاد العربية، حتى أصبح لدى هؤلاء العلماء القدرة على كتابة القرآن الكريم باللغة العربية؛ ولذلك فقد دخلت في اللغة الملايوية كلمات عربية كثيرة متعلقة بالدين الإسلامي وغيره. يتبع الباحث المنهجين الوصفي والمقارن لبيان مدى تأثر الأدب الملايوي بالتراثين العربي والغربي، وقد توصل البحث إلى نتائج، منها: أن الإسلام أدى دوراً مهماً في تكوين ثقافة شعب أرخبيل الملايو؛ لذا أصبح تأثير اللغة العربية واضحاً وقوياً في اللغة الملايوية، إلى درجة أنها كانت تكتب بالحروف الهجائية العربية "الجاوية"، واكتشف العلماء الملايويين فداحة الموقف؛ لأنهم شاهدوا بأعينهم التأثير السيء للثقافة الغربية في أبنائهم؛ لأن هذه الثقافة تتنافى مع تعاليم الدين الإسلامي السمحة، فبدأ هؤلاء العلماء في محاولة تنظيف مجتمعهم من آثار الثقافة الغربية السلبية، وأصبحوا يهتمون بالثقافة الإسلامية والعربية. = This article attempts to discuss on the influence of the Arabic and English in Malay. The initial influence was from Arabic evidently from the numerous loan words it took from it in addition to the Arabic scripts known as Jawi due to influx of Malay scholars who learned Arabic and religious studies in the Arab world that enable them to write the Quran in Arabic that would subsequently Islamic terms and other loan words to enter the Malay word stock. The paper follows descriptive and comparative methods to explain the extent of influence of both traditions. Among the conclusions of the paper are: Islam played a very significant role in constructing the Malay culture and this is apparent in the strong presence of its influence in Malay that is was once written in the Arabic scripts. The Western influence was seen negatively by some Islamic scholars as many considered it to be in contradiction to the Islamic teachings. This had initiated the efforts to clean up the society from this negative influence and revert to the Arabic Islamic culture that once had its strong foothold in the Malay culture.